Empowering Educators: The Impact of Principal Leadership and Supervision on Teacher Performance at Ulu Tulisi Private Madrasah Aliyah - Sari, Widya Maya; Wandra, Novera; Bismark, O. P.; Dakhyar, Dakhyar; Putra, Mandra Adrika (CV. Strata Persada Academia, 2024)
This research investigates the influence of principal supervision and leadership on teacher performance at Ulu Tulisi Private Madrasah Aliyah. The Indonesian government prioritizes improving education quality, and teacher performance is a crucial factor. Previous research highlights the importance of principal supervision and leadership for teacher performance. However, the effectiveness of these aspects at Ulu Tulisi Private Madrasah Aliyah remains unclear. This study aims to identify how principal supervision and leadership influence teacher performance at this madrasah. This quantitative descriptive research employed questionnaires and document analysis to collect data from teachers at Ulu Tulisi Private Madrasah Aliyah. The research instruments were assessed for validity and reliability using logical validity and Cronbach's Alpha formula, respectively. Descriptive statistics and multiple regression analysis were used to analyze the data and determine the effects of principal supervision and leadership on teacher performance. The findings indicate that principal supervision and leadership are perceived favorably by teachers. However, only principal leadership has a statistically significant positive influence on teacher performance. These results suggest that the principal's leadership style plays a more prominent role in enhancing teacher performance at Ulu Tulisi Private Madrasah Aliyah compared to supervision practices.